MEDICAL STUDENTS INFORMATIONS MANAGEMENTS COMPETENCE - Hanifa, Sepwinda A; Meidianawaty, Vivi; Sutisna, Atik (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
In order to be able to learn and make the right decisions, a doctor can utilize information management skills. It is also important for medical students who will become doctors to have information management skills. Medical students’ ability to solve problems and make logical decisions is due to good information management skills. This research is a cross sectional study with stratified random sampling. The minimum sample required is 89 people taken from preclinical stage 1,2,3 and 4 and clinical stage of medical students Faculty of Medicine Swadaya Gunung Jati University (FK UGJ). Spearman’s test shows a p value of 0,650 on the evaluating sub variable. This means that evaluating has a strong relationship and has a positive value. The ability to evaluate information of FK UGJ students at the preclinical and clinical stage has a strong and positive relationship with the ability to manage information. High ability to evaluate the information reflects high ability to manage information.